2014
DOI: 10.7727/wimj.2013.059
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Interantral Bone in Implant Dentistry using Panoramic Radiography and Cone-Beam Computed Tomography: a Human Radiographic Study

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
(19 reference statements)
0
10
0
Order By: Relevance
“…The image is largely affected by the body position with variable magnification rates and distortion rates for different parts [ 19 , 20 ]. Previously, panoramic radiography is shown to be a sufficiently accurate method to obtain the interatral bone height in the incisor area, but not in the canine area as compared with CBCT [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The image is largely affected by the body position with variable magnification rates and distortion rates for different parts [ 19 , 20 ]. Previously, panoramic radiography is shown to be a sufficiently accurate method to obtain the interatral bone height in the incisor area, but not in the canine area as compared with CBCT [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…25 Kopecka et al reported that, OPG doesn't give accurate results in alveolar bone height measurements in the maxillary canine region when compared to CBCT. 26 They concluded that it offers more consistent results with CBCT in maxillary incisor region. In the present study, we also found a weak correlation between two methods in NF group.…”
Section: Discussionmentioning
confidence: 96%
“…Radiography is carried out for evaluating the quantity and morphology of the remaining peri-implant alveolar bone and its surrounding anatomical structures, especially the position of the IAN and the maxillary sinus. (14,15) Some studies have assessed the IAN damage after placing an implant in the mandibular bone. (16-26) Lin et al studied the IAN damage during immediate implantation.…”
Section: Discussionmentioning
confidence: 99%
“…The patients (n=100) included 43 women and 57 men, averagely 53 years old, who experienced neurosensory changes 10 days after implantation, and panoramic radiographs (CRANEX® D Panoramic Dental X-Ray Machine, Soredex, Orion Co. Ltd., Helsinki, Finland) were taken as soon as they reported the neural changes. (14)(15)(16) The purpose of the study was explained to the patients, and written informed consent forms were received.…”
Section: Methodsmentioning
confidence: 99%